JERLING, Jacobus Daniël Inventory of documents - JERLING, Jacobus Daniël (ARCA, 2018)
Private paper of J.D. Jerling, member of the Ossewa-Brandwag, with the rank of Assistant-Commandant-General.
COVERAGE 1914-1967; 37 Files; 0,78 Metres.
Keywords: JERLING, Jacobus Daniël; Inventories; Ossewa Brandwag